Study on the suppression of pyrolytic gas flames in red pine wood by water mist - Li Haoyang; Jinyuan Hao; Zhiming Du; Tianwei Zhang (Case Studies in Thermal Engineering, 2022)
The suppression of forest fires has been one of the important research directions in the field of fire safety, fine water mist because of the advantages of easy access to materials, low price and no pollution to become one of the commonly used inhibitors to suppress forest fires, so previous research done for fine water mist suppression of forest fires, mostly for the macro level of fire suppression effectiveness and methodological research, for fine water mist and forest fire interaction mechanism research is less, this paper for the convenience of research, the In this paper, to facilitate the study of red pine wood as the research object, after high temperature pyrolysis analysis of pyrolysis gas components, the construction of fine water mist suppression of red pine wood pyrolysis gas flame Bunsen burner experimental system, study the effect of different additions of fine water mist on the laminar flame speed (SL) of red pine wood pyrolysis gas flame, and the use of chemkin software to study the mechanism of interaction between fine water mist and red pine wood pyrolysis gas flame, on the study of the interaction between fine water mist and red pine pyrolysis gas flames using chemkin software has some implications for the suppression of forest fires. In this paper, the pyrolysis gas products of red pine wood were firstly analysed by TG-DSC as well as GC/MS and found to consist mainly of H2, CO2, C2H4, CO, CH4, C2H6, C3H6 and C3H8, accounting for more than 98% of the gases. The Bunsen burner experimental system constructed for the suppression of red pine pyrolysis gas flames by fine water mist revealed that the flame height gradually increased with increasing fine water mist addition and the flame cone angle gradually decreased, indicating that the flame speed was gradually decreasing with increasing fine water mist addition. It was observed that the flame height did not change significantly at low equivalents as the amount of extinguishing agent added increased, indicating that the fine water mist had a weak pro-ignition effect on the red pine pyrolysis gas/air system. The influence of the gas content on the flame promotion effect of the fine water mist was investigated by chemkin software. It was found that the ratio of CO/H2 in the pyrolysis gas composition of red pine wood will determine the strength of the combustion promoting effect of the fine water mist in the interaction with the pyrolysis gas flame, the higher the ratio of CO/H2, the stronger the combustion promoting effect of the fine water mist in the interaction with the pyrolysis gas flame, and conversely the lower the ratio, the weaker the combustion promoting effect of the fine water mist in the interaction with the pyrolysis gas flame.